2018
DOI: 10.1002/esp.4355
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent flow structures and geomorphic characteristics of a mining affected alluvial channel

Abstract: Sediment mining in rivers may have a major impact on river geomorphology and research is required to quantify these impacts. In this research, experimental studies were conducted to analyse the morphological changes of channel bed and the turbulent characteristics of flow in the presence of mining. The channel bed profile shows erosion at the bank of the pit and that the erosion expands to the whole width of the channel and propagates downstream with time. The deposition of sediment occurs along the upstream e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(18 citation statements)
references
References 28 publications
0
17
0
1
Order By: Relevance
“…The HEC-RAS model predicted heavy erosion on the upstream side of the pit, while CCHE2D predicted relatively higher downstream erosion. Experiments conducted by Barman et al [8] reported a rise in the turbulent stresses in the mining pit and at the downstream side of the pit.…”
Section: Introductionmentioning
confidence: 99%
“…The HEC-RAS model predicted heavy erosion on the upstream side of the pit, while CCHE2D predicted relatively higher downstream erosion. Experiments conducted by Barman et al [8] reported a rise in the turbulent stresses in the mining pit and at the downstream side of the pit.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past century, anthropogenic pressures associated with population growth, urbanisation, and economic development have seen an increase in the demand for the natural resources river systems provide Best and Darby, 2020). In particular, the demand for sand and gravel from rivers has seen unprecedented growth since the 1970s (Peduzzi, 2014;Miatto et al, 2017;Torres et al, 2017), with demand now outstripping supply (Bendixen et al, 2019). Estimates indicate that today, at a minimum, between 32 and 50 × 10 9 t of aggregates are extracted globally every year (Koehnken and Rintoul, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In order to effectively and sustainably manage riverine sand resources, accurate and regular monitoring of the locations and rates of sediment extraction are required (Peduzzi, 2014;Bendixen et al, 2019). Yet the pervasive and diffuse nature of the riverine extraction process means that it often occurs at spatial scales (spread across many square kilometres of river surface area) and in remote locations that make on-site monitoring difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Mining practices frequently target sediment from stores of sand (bedforms) on the river bed 22,23 . The removal of sand has been shown to alter the riverbed morphology, reduce flow velocities and increase flow turbulence around the mining pit areas 23,24 , sometimes with undesirable impacts. For example, there has been speculation that perceived increases in rates of bank erosion are caused by sand mining 8,14,23 -26 .…”
mentioning
confidence: 99%